2013
DOI: 10.1080/01904167.2013.799183
|View full text |Cite
|
Sign up to set email alerts
|

Response of a Cool-Season Turf Mixture to Composted Chicken Manure in a Mediterranean Environment

Abstract: 2 The current study addresses the effects of topdressing composted chicken manure on established turf and comparing the composted chicken manure to a chemical nitrogen (N) fertilizer. Turf color, quality and clipping yields were correlated with N sources and application timing. Monthly fertilization resulted in a more uniform color and turf quality and less clipping yields than did comparable amounts of all N sources applied each as a single application in spring and spring and fall (S + F). The monthly and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Compost benefits are increased with time. Bilgili et al (2013) found that the monthly and/or spring + fall top dressing of compost increased the color and quality ratings of the turf mixture. Ntoulas et al (2011) evaluated the influence of compost on the establishment rate of Cynodon dactylon and showed that the clipping dry weights were increased by using compost amendments.…”
Section: Introductionmentioning
confidence: 94%
“…Compost benefits are increased with time. Bilgili et al (2013) found that the monthly and/or spring + fall top dressing of compost increased the color and quality ratings of the turf mixture. Ntoulas et al (2011) evaluated the influence of compost on the establishment rate of Cynodon dactylon and showed that the clipping dry weights were increased by using compost amendments.…”
Section: Introductionmentioning
confidence: 94%